Peran Budaya Literasi Dalam Meningkatkan Minat Baca Siswa Di Sekolah Dasar: Analisis Review - Nuralysa, Wanda; Fadilah, Siti Nur; Riskianti, Yasmin Arin; Pipiot, Riska A; Ombitaka, Jessicka Klaratin (JURNAL DIKDAS, 2025)
The aim of this research is to determine the role of school literacy activity programs, obstacles and efforts in increasing students' interest in reading in elementary schools. This research method is a systematic literature review (SLR) method using a descriptive qualitative approach, with research subjects being school principals, teachers and students. Data collection techniques are through interviews, observation and documentation. Data analysis techniques include data collection, data reduction, data display and conclusion. Based on the data obtained, it shows that: The literacy culture implemented in schools plays an important role in students' interest in reading, obstacles in carrying out literacy activities at school and the efforts made by the school to overcome obstacles. The results of this research conclude that The School Literacy Movement can increase students' interest in reading in elementary schools